2019
DOI: 10.11144/javeriana.upsy18-3.vrer
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Revised Ego-Resiliency Scale in a High-Vulnerable Colombian Population

Abstract: The ER89 (Block & Kremen, 1996) is a self-report scale measuring ego-resiliency in community contexts. The present study examined the psychometric properties of a brief version of the ER 89 (ER89-R: Alessandri, Vecchio, Steca, Caprara, & Caprara, 2007) in a Colombian high-vulnerable population. Participants were 947 young and adults (427 males, 520 females), ranging in age from 16 to 66 years (M = 32.4, SD = 11.6), living in fourteen town halls and beneficiaries of four programs for individuals in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Winning FISM can be considered such a success. Taking into consideration the relation between ego-resiliency and self-esteem, similar results of ego-resiliency (in general) as correlating factor and predictor were obtained by Vecchio et al (2019), and a positive correlation between those two dimensions was also obtained by Caprara et al (2003). In the cited studies, the ego-resiliency dimensions were not predictors of self-esteem -despite the fact that the dimensions of the ego-resiliency correlate with self-esteem in the studied group.…”
Section: Discussionsupporting
confidence: 61%
“…Winning FISM can be considered such a success. Taking into consideration the relation between ego-resiliency and self-esteem, similar results of ego-resiliency (in general) as correlating factor and predictor were obtained by Vecchio et al (2019), and a positive correlation between those two dimensions was also obtained by Caprara et al (2003). In the cited studies, the ego-resiliency dimensions were not predictors of self-esteem -despite the fact that the dimensions of the ego-resiliency correlate with self-esteem in the studied group.…”
Section: Discussionsupporting
confidence: 61%
“…In subsequent use, researchers have developed a shorter, revised version of the ER89-R [28]. In studies using the ER89-R, the results showed full configural invariance for different age groups (16-25 years, 26-40 years, and 40+ years), indicating that the scale demonstrated appropriate testing power across age groups to accurately measure self-resilience as a psychological quality [29].…”
Section: Measurement Of Resiliencementioning
confidence: 99%